Adhesive taking waste edible oil as raw material and preparation method of adhesive
By modifying waste edible oil and combining it with other materials, an adhesive with excellent adhesive properties and water resistance is prepared, which solves the problems of poor performance and poor water resistance of existing adhesives, and achieves a green and environmentally friendly high-performance bonding effect.
Patent Information
- Application Number
- CN202411907864.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-08
AI Technical Summary
Existing adhesives have poor performance and poor water resistance, making it difficult to maintain long-term effective adhesion in various environments.
Using a binder with waste edible oil as the raw material, a binder with excellent adhesive properties and water resistance is prepared by modifying the waste edible oil and combining it with asphalt, dispersant, organic montmorillonite and other materials.
A green and environmentally friendly bio-based adhesive with high adhesion strength and high water resistance has been achieved, which solves the problem of poor performance of traditional adhesives, is suitable for the bonding of multiple materials, and reduces environmental pollution.
Smart Images

Figure CN119775958A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waste resource utilization, and specifically relates to an adhesive using waste edible oil as a raw material and a preparation method thereof. Background Art
[0002] Waste cooking oil refers to waste oil that has lost its edible value. It contains a large amount of carbon-containing organic matter such as fatty acids and has a certain recycling value. Converting waste cooking oil into high-value materials is conducive to alleviating social problems such as energy crisis and environmental pollution. It also provides a rational utilization method for waste cooking oil and helps prevent waste cooking oil from entering the food chain. It has a good development prospect.
[0003] As an important and indispensable material, adhesives are widely used in aerospace, automobile, wood furniture industry, medicine and other fields. Traditional adhesives are generally resins, such as epoxy resin, formaldehyde resin and phenolic resin, which are mainly derived from non-renewable petroleum resources and produce volatile harmful substances such as formaldehyde, which are harmful to human health and pollute the environment. This has prompted researchers to increase the development of green, renewable, non-toxic and high-performance bio-based adhesives, which have shown great potential in replacing formaldehyde-based adhesives.
[0004] However, in actual use, the environment faced by adhesives is usually variable. The change from a dry environment to an aqueous environment is the most common and challenging. Maintaining long-term effective adhesion in harsh environments such as seawater, acid, alkali, and organic solvents is a big challenge. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide an adhesive using waste cooking oil as raw material and a preparation method thereof, and to prepare the adhesive using waste cooking oil as raw material to solve the problem of poor performance and poor water resistance of the current adhesive.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The invention provides an adhesive using waste edible oil as a raw material. Calculated by mass percentage, the adhesive consists of 50-60% of waste edible oil, 20-30% of asphalt, 2-5% of dispersant, 2-5% of organic montmorillonite, 5%-10% of styrene-butadiene rubber, 1%-3% of solubilizer, 1%-2% of crosslinking agent, 1%-2% of anti-aging agent and 5%-10% of petroleum resin.
[0008] Furthermore, the adhesive consists of 55% waste cooking oil, 25% asphalt, 3.5% dispersant, 3.5% organic montmorillonite, 7% styrene-butadiene rubber, 2% solubilizer, 1.5% cross-linking agent, 1.5% anti-aging agent, and 7.5% petroleum resin.
[0009] Furthermore, the asphalt is petroleum asphalt, the dispersant is didecyl dimethyl ammonium chloride, the solubilizer is one or more combinations of polyethylene glycol and polysorbate; the cross-linking agent is one or more of glutaraldehyde, acetic anhydride, diglycidyl ethyl ether, methyl succinimidyl, epichlorohydrin, and N,N-methylenebisacrylamide; and the anti-aging agent is chloroprene rubber.
[0010] Furthermore, a method for preparing an adhesive using waste edible oil as a raw material comprises the following steps:
[0011] S1. Modifying the waste cooking oil and mixing it with asphalt, dispersant and organic montmorillonite to obtain an initial viscous substance;
[0012] S2, then continue to add styrene-butadiene rubber, solubilizer, cross-linking agent and antioxidant and continue to stir;
[0013] S3. Finally, petroleum resin is added to increase viscosity, and the adhesive is obtained after development under high-speed shear and constant temperature conditions.
[0014] Furthermore, in step S1, the modification step of the waste cooking oil is:
[0015] P1. Filter the waste cooking oil to remove coarse impurities;
[0016] P2. Add formic acid and concentrated sulfuric acid to the waste cooking oil, heat it in a water bath to 55-60°C, then add 30% H2O2, add 5% NaHCO3 solution after the reaction and wash until neutral, separate the cooking oil after standing and stratifying, and rotary evaporate the cooking oil;
[0017] P3. After rotary evaporation, continue to add tannic acid solution and citric acid, and after the reaction is complete, the modified edible oil is obtained.
[0018] Furthermore, in step P3, the mass ratio of the edible oil, the tannic acid solution and the citric acid after rotary evaporation is 10:3-6:3-6.
[0019] Furthermore, in the steps S1 and S2, the reaction conditions are 40-48°C, and in the step S3, the high-speed shear rate is 300-500 rpm / min, and the constant temperature is 28-35°C.
[0020] Furthermore, in step P2, the mass ratio of waste cooking oil, 30% H2O2, formic acid and concentrated sulfuric acid is 1:0.7:0.2:0.05.
[0021] Furthermore, in step P3, the tannic acid solution may also be an ethanol solution with a concentration of 0.5 g / ml.
[0022] The beneficial effects of the present invention are:
[0023] 1. The adhesive prepared by the present invention has excellent adhesive properties and water resistance. By converting waste oil into valuable materials and using sustainable sources to prepare it, a green and environmentally friendly bio-based adhesive with high adhesion strength and high water resistance is obtained, which solves the problems existing in traditional adhesives. The present invention can not only realize the resource utilization of waste, but also reduce environmental pollution and reduce the cost of garbage disposal. The waste cooking oil of the present invention has a wide source and low price. The prepared adhesive has a low cost and has broad market prospects. By adjusting the raw material ratio and preparation conditions in the formula, adhesives with different viscosities and curing times can be prepared to meet the needs of different customers.
[0024] 2. When modifying waste cooking oil, the present invention adjusts the ratio of waste cooking oil, citric acid and tannic acid, and prepares the adhesive through heating and cross-linking reaction. The adhesive has high adhesion and water resistance and can be applied to a variety of materials.
[0025] 3. In the present invention, the phenolic substances in asphalt, when in contact with other substances, will react with the active groups on the surface of certain materials to form more stable chemical bonds, thereby improving adhesion. In addition, the asphalt will undergo a cross-linking reaction after heating or adding a catalyst to form a network structure, thereby improving the bonding strength. The addition of petroleum resin can further improve the viscosity of the adhesive.
[0026] 4. In the present invention, the dispersant and the organic montmorillonite can be used to improve the dispersibility of waste cooking oil and asphalt, and didecyl dimethyl ammonium chloride also has a bactericidal effect, which can play a strong bactericidal effect. Styrene-butadiene rubber, solubilizer and can improve the flexibility and water resistance of the adhesive, while the crosslinking agent and anti-aging agent can enhance the crosslinking degree and anti-aging performance of the adhesive.
[0027] Other advantages, objectives and features of the present invention will be described in the following description and will be apparent to those skilled in the art to some extent, or those skilled in the art may be taught from the practice of the present invention. The objectives and other advantages of the present invention may be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to make the purpose, technical solution and beneficial effects of the invention clearer, the present invention provides the following drawings for illustration:
[0029] Figure 1 This is a SEM image of the adhesive of Example 1 of the present invention;
[0030] Figure 2 This is a scanning electron microscope image of the adhesive of Example 1 of the present invention after being pulled to failure;
[0031] Figure 3 This is a schematic diagram of the adhesive bonding steel plates in Example 1 of the present invention;
[0032] Figure 4 This is a test diagram of water resistance performance of Example 1 of the present invention under different conditions;
[0033] Figure 5 This is the infrared spectrum of the adhesive during modification according to the present invention. DETAILED DESCRIPTION
[0034] Figure 1-Figure 5 As shown, an adhesive using waste cooking oil as raw material and a preparation method thereof.
[0035] Example 1
[0036] S1. Filter the waste cooking oil to remove food residues, and obtain clear and transparent waste cooking oil for later use;
[0037] S2. Weigh the waste cooking oil in a three-necked flask, add formic acid and a small amount of concentrated sulfuric acid, heat in a water bath at 60°C, slowly add 30% H2O2 within 15 minutes, and then stir continuously at a constant temperature for 6 hours. The mass ratio of waste cooking oil, 30% H2O2, formic acid, and concentrated sulfuric acid is 1:0.7:0.2:0.05;
[0038] S3, after the reaction is completed, the temperature is lowered and cooled, and then washed with 5% NaHCO3 solution until the pH is 5, and then washed with pure water until neutral, allowed to stand and stratify, the upper layer solution is taken, and rotary evaporated to obtain epoxy waste oil;
[0039] S4. Weigh the epoxy waste oil into a three-necked beaker, add 0.5 g / ml tannic acid, heat the oil bath to 70°C, react and mix for 5 minutes, then add citric acid, continue stirring and reacting for 3 hours to obtain modified waste edible oil; the mass ratio of waste edible oil, citric acid and tannic acid is 10:3:4;
[0040] S5. At 45°C, 55% of the modified waste cooking oil by mass, 25% of asphalt, 3.5% of the dispersant, and 3.5% of the organic montmorillonite were mixed evenly to obtain an initial viscous substance;
[0041] S6, then continue to add 7% styrene-butadiene rubber, 2% solubilizer, 1.5% cross-linking agent and 1.5% anti-aging agent and continue stirring;
[0042] S7. Finally, 7.5% petroleum resin is added to increase viscosity and mixed, and high-speed shearing is carried out at 400 rpm / min at 30°C to obtain an adhesive.
[0043] Example 2
[0044] S1. Filter the waste cooking oil to remove food residues, and obtain clear and transparent waste cooking oil for later use;
[0045] S2. Weigh the waste cooking oil in a three-necked flask, add formic acid and a small amount of concentrated sulfuric acid, heat in a water bath at 60°C, slowly add 30% H2O2 within 15 minutes, and then stir continuously at a constant temperature for 6 hours. The mass ratio of waste cooking oil, 30% H2O2, formic acid, and concentrated sulfuric acid is 1:0.7:0.2:0.05;
[0046] S3, after the reaction is completed, the temperature is lowered and cooled, and then washed with 5% NaHCO3 solution until the pH is 5, and then washed with pure water until neutral, allowed to stand and stratify, the upper layer solution is taken, and rotary evaporated to obtain epoxy waste oil;
[0047] S4. Weigh the epoxy waste oil into a three-necked beaker, add 0.5 g / ml tannic acid, heat the oil bath to 70°C, react and mix for 5 minutes, then add citric acid, continue stirring and reacting for 3 hours to obtain modified waste edible oil; the mass ratio of waste edible oil, citric acid and tannic acid is 10:3:4;
[0048] S5. At 45°C, 50% of the modified waste cooking oil by mass, 20% of asphalt, 2% of the dispersant, and 2% of the organic montmorillonite were mixed evenly to obtain an initial viscous substance;
[0049] S6, then continue to add 10% styrene-butadiene rubber, 3% solubilizer, 1% cross-linking agent and 2% anti-aging agent and continue stirring;
[0050] S7. Finally, 10% petroleum resin is added to increase viscosity and mixed, and high-speed shearing is carried out at 400 rpm / min at 30°C to obtain an adhesive.
[0051] The difference between Example 2 and Example 1 is that the mass percentage of the materials is changed, but both are within the scope of the present invention.
[0052] Example 3
[0053] S1. Filter the waste cooking oil to remove food residues, and obtain clear and transparent waste cooking oil for later use;
[0054] S2. Weigh the waste cooking oil in a three-necked flask, add formic acid and a small amount of concentrated sulfuric acid, heat in a water bath at 60°C, slowly add 30% H2O2 within 15 minutes, and then stir continuously at a constant temperature for 6 hours. The mass ratio of waste cooking oil, 30% H2O2, formic acid, and concentrated sulfuric acid is 1:0.7:0.2:0.05;
[0055] S3, after the reaction is completed, the temperature is lowered and cooled, and then washed with 5% NaHCO3 solution until the pH is 5, and then washed with pure water until neutral, allowed to stand and stratify, the upper layer solution is taken, and rotary evaporated to obtain epoxy waste oil;
[0056] S4. Weigh the epoxy waste oil into a three-necked beaker, add 0.5 g / ml tannic acid, heat the oil bath to 70°C, react and mix for 5 minutes, then add citric acid, continue stirring and reacting for 3 hours to obtain modified waste edible oil; the mass ratio of waste edible oil, citric acid and tannic acid is 10:3:4;
[0057] S5. At 45°C, 60% of the modified waste cooking oil by mass, 20% of asphalt, 5% of the dispersant, and 3% of the organic montmorillonite were mixed evenly to obtain an initial viscous substance;
[0058] S6, then continue to add 5% styrene-butadiene rubber, 3% solubilizer, 2% cross-linking agent and 1% anti-aging agent and continue stirring;
[0059] S7. Finally, 5% petroleum resin is added to increase viscosity and mixed, and high-speed shearing is carried out at 400 rpm / min at 30°C to obtain an adhesive.
[0060] The difference between Example 3 and Example 1 is that the mass percentage of the materials is changed, but both are within the scope of the present invention.
[0061] Example 4
[0062] Except that the mass ratio of waste cooking oil, citric acid and tannic acid is changed to 10:5:4, the rest is the same as Example 1.
[0063] Example 5
[0064] Except that the mass ratio of waste cooking oil, citric acid and tannic acid is changed to 10:4:5, the rest is the same as Example 1.
[0065] Example 6
[0066] Except that the mass ratio of waste cooking oil, citric acid and tannic acid is changed to 10:3:6, the rest is the same as Example 1.
[0067] Example 7
[0068] Except that the mass ratio of waste cooking oil, citric acid and tannic acid is changed to 10:6:3, the rest is the same as Example 1.
[0069] The present invention explores the influence of the change of the percentage of other materials under the same waste edible oil modification conditions and the change of the waste edible oil modification conditions under the same percentage of other materials within the protection scope on the strength of the adhesive. The adhesives of Examples 1 to 7 were applied to the surface of the steel sheet, heated at 180°C for 1 hour, and then the surfaces of the two steel sheets were bonded, compacted, and cured at 180°C for 6 hours. The performance test was performed, and the results are shown in Table 1:
[0070] Table 1
[0071]
[0072] In order to prove the superiority of the raw materials, proportions and methods of the present invention, comparative examples 1 to 4 are set up.
[0073] Comparative Example 1
[0074] S1. Mix 55% of waste cooking oil, 25% of asphalt, 3.5% of dispersant and 3.5% of organic montmorillonite at 45°C.
[0075] S6, then continue to add 7% styrene-butadiene rubber, 2% solubilizer, 1.5% cross-linking agent and 1.5% anti-aging agent and continue stirring;
[0076] S7. Finally, 7.5% petroleum resin is added to increase viscosity and mixed, and high-speed shearing is carried out at 400 rpm / min at 30°C to obtain an adhesive.
[0077] The difference between Comparative Example 1 and Example 1 is that the waste cooking oil is not modified.
[0078] Comparative Example 2
[0079] S1. Filter the waste cooking oil to remove food residues, and obtain clear and transparent waste cooking oil for later use;
[0080] S2. Weigh the waste cooking oil in a three-necked flask, add formic acid and a small amount of concentrated sulfuric acid, heat in a water bath at 60°C, slowly add 30% H2O2 within 15 minutes, and then stir continuously at a constant temperature for 6 hours. The mass ratio of waste cooking oil, 30% H2O2, formic acid, and concentrated sulfuric acid is 1:0.7:0.2:0.05;
[0081] S3, after the reaction is completed, the temperature is lowered and cooled, and then washed with 5% NaHCO3 solution until the pH is 5, and then washed with pure water until neutral, allowed to stand and stratify, the upper layer solution is taken, and rotary evaporated to obtain epoxy waste oil;
[0082] S4. Weigh the epoxy waste oil into a three-necked beaker, add 0.5 g / ml tannic acid, heat the oil bath to 70°C, react and mix for 5 minutes, then add citric acid, continue stirring and reacting for 3 hours to obtain modified waste edible oil; the mass ratio of waste edible oil, citric acid and tannic acid is 10:3:4;
[0083] S5. At 45°C, 92.5% of the modified waste cooking oil, 3.5% of the dispersant and 3.5% of the organic montmorillonite were mixed evenly;
[0084] S6, then continue to add 7% styrene-butadiene rubber, 2% solubilizer, 1.5% cross-linking agent and 1.5% anti-aging agent and continue to stir, and develop at 30°C at a high-speed shear rate of 400 rpm / min to obtain an adhesive.
[0085] The difference between Comparative Example 2 and Example 1 is that raw materials such as asphalt and petroleum resin are not added.
[0086] Comparative Example 3
[0087] S1. Filter the waste cooking oil to remove food residues, and obtain clear and transparent waste cooking oil for later use;
[0088] S2. Weigh the waste cooking oil in a three-necked flask, add formic acid and a small amount of concentrated sulfuric acid, heat in a water bath at 60°C, slowly add 30% H2O2 within 15 minutes, and then stir continuously at a constant temperature for 6 hours. The mass ratio of waste cooking oil, 30% H2O2, formic acid, and concentrated sulfuric acid is 1:0.7:0.2:0.05;
[0089] S3, after the reaction is completed, the temperature is lowered and cooled, and then washed with 5% NaHCO3 solution until the pH is 5, and then washed with pure water until neutral, allowed to stand and stratify, the upper layer solution is taken, and rotary evaporated to obtain epoxy waste oil;
[0090] S4. Weigh the epoxy waste oil into a three-necked beaker, add 0.5 g / ml tannic acid, heat in an oil bath to 70°C, react and mix for 5 minutes, then add citric acid, continue stirring and reacting for 3 hours to obtain modified waste edible oil; the mass ratio of waste edible oil, citric acid and tannic acid is 10:10:10;
[0091] S5. At 45°C, 55% of the modified waste cooking oil by mass, 25% of asphalt, 3.5% of the dispersant, and 3.5% of the organic montmorillonite were mixed evenly to obtain an initial viscous substance;
[0092] S6, then continue to add 7% styrene-butadiene rubber, 2% solubilizer, 1.5% cross-linking agent and 1.5% anti-aging agent and continue stirring;
[0093] S7. Finally, 7.5% petroleum resin is added to increase viscosity and mixed, and high-speed shearing is carried out at 400 rpm / min at 30°C to obtain an adhesive.
[0094] The difference between Comparative Example 3 and Example 1 is that the mass ratio of waste cooking oil, citric acid and tannic acid is 10:10:10.
[0095] Comparative Example 4
[0096] S1. Filter the waste cooking oil to remove food residues, and obtain clear and transparent waste cooking oil for later use;
[0097] S2. Weigh the waste cooking oil in a three-necked flask, add formic acid and a small amount of concentrated sulfuric acid, heat in a water bath at 60°C, slowly add 30% H2O2 within 15 minutes, and then stir continuously at a constant temperature for 6 hours. The mass ratio of waste cooking oil, 30% H2O2, formic acid, and concentrated sulfuric acid is 1:0.7:0.2:0.05;
[0098] S3, after the reaction is completed, the temperature is lowered and cooled, and then washed with 5% NaHCO3 solution until the pH is 5, and then washed with pure water until neutral, allowed to stand and stratify, the upper layer solution is taken, and rotary evaporated to obtain epoxy waste oil;
[0099] S4. Weigh the epoxy waste oil into a three-necked beaker, add 0.5 g / ml tannic acid, heat the oil bath to 70°C, react and mix for 5 minutes, then add citric acid, continue stirring and reacting for 3 hours to obtain modified waste edible oil; the mass ratio of waste edible oil, citric acid and tannic acid is 10:3:4;
[0100] S5. At 45°C, 40% of the modified waste cooking oil, 40% of asphalt, 8% of the dispersant, and 1% of the organic montmorillonite were mixed evenly to obtain an initial viscous substance;
[0101] S6, then continue to add 5% styrene-butadiene rubber, 2% solubilizer, 1% cross-linking agent and 1% anti-aging agent and continue stirring;
[0102] S7. Finally, 2% petroleum resin is added to increase viscosity and mixed, and high-speed shearing is carried out at 400 rpm / min at 30°C to obtain an adhesive.
[0103] The difference between Comparative Example 1 and Example 1 is that the modification conditions of the waste cooking oil are the same, and the mass percentages of the remaining materials are changed, which are not within the scope of the present application.
[0104] The present invention explores the influence on the strength of the adhesive when the waste cooking oil is not modified, the modification conditions are changed, and the percentages and ingredients of the remaining materials are not completely the same. The adhesives of Comparative Examples 1 to 4 are applied to the surface of the steel sheet, heated at 180°C for 1 hour, and then the surfaces of the two steel sheets are bonded, compacted, and cured at 180°C for 6 hours. The performance test is performed, and the results are shown in Table 2:
[0105] Table 2
[0106]
[0107] It can be seen from Table 1 that within the scope of the present invention, even if the raw materials and the proportions are changed, the adhesive bonding strength performance is still excellent, the bonding strength to the object is high, and it can be applied to the bonding of various materials.
[0108] It can be seen from Table 2 that the waste cooking oil is not modified, or the waste cooking oil, citric acid and tannic acid are not within the scope of the present invention during modification, or the changes in the other raw materials and the changes in the raw material ratios do not lead to poor performance of the adhesive and inability to effectively bond objects.
[0109] Figure 1 is the SEM image of the adhesive. Figure 2This is a scanning electron microscope image of the adhesive after it was pulled to failure; Figure 5 The infrared spectrum of the waste edible oil modified according to the present invention is shown.
[0110] like Figure 3 , Figure 4 As shown, the adhesives prepared in Examples 1 to 7 of the present invention are placed in different liquid environments (pure water solution, NaOH solution, HCl solution, NaCl solution, boiling water solution). It can be seen that even after being immersed in different solutions, the steel plates bonded with the adhesive of the present invention still have excellent adhesion.
[0111] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. An adhesive using waste cooking oil as raw material, characterized in that: Calculated by mass percentage, the adhesive consists of 50-60% waste cooking oil, 20-30% asphalt, 2-5% dispersant, 2-5% organic montmorillonite, 5%-10% styrene-butadiene rubber, 1%-3% solubilizer, 1%-2% crosslinking agent, 1%-2% anti-aging agent, and 5%-10% petroleum resin.
2. The adhesive made of waste cooking oil as raw material according to claim 1, characterized in that: The adhesive consists of 55% of waste edible oil, 25% of asphalt, 3.5% of dispersant, 3.5% of organic montmorillonite, 7% of styrene-butadiene rubber, 2% of solubilizer, 1.5% of crosslinking agent, 1.5% of anti-aging agent and 7.5% of petroleum resin.
3. The adhesive made of waste edible oil as raw material according to claim 1, characterized in that: The asphalt is petroleum asphalt, the dispersant is didecyl dimethyl ammonium chloride, the solubilizer is one or more combinations of polyethylene glycol and polysorbate; the cross-linking agent is one or more of glutaraldehyde, acetic anhydride, diglycidyl ethyl ether, methyl succinimidyl, epichlorohydrin, and N,N-methylenebisacrylamide; and the anti-aging agent is chloroprene rubber.
4. The adhesive using waste edible oil as raw material according to any one of claims 1 to 3, further comprising a method for preparing the adhesive using edible oil as raw material, characterized in that: The following steps are included: S1. Modifying the waste cooking oil and mixing it with asphalt, dispersant and organic montmorillonite to obtain an initial viscous substance; S2, then continue to add styrene-butadiene rubber, solubilizer, cross-linking agent and antioxidant and continue to stir; S3. Finally, petroleum resin is added to increase viscosity, and the adhesive is obtained after development under high-speed shear and constant temperature conditions.
5. The method for preparing an adhesive using waste edible oil as raw material according to claim 4, characterized in that: In step S1, the modification step of the waste cooking oil is: P1. Filter the waste cooking oil to remove coarse impurities; P2. Add formic acid and concentrated sulfuric acid to the waste cooking oil, heat it in a water bath to 55-60°C, then add 30% H2O2, add 5% NaHCO3 solution after the reaction and wash until neutral, separate the cooking oil after standing and stratifying, and rotary evaporate the cooking oil; P3. After rotary evaporation, continue to add tannic acid solution and citric acid, and after the reaction is complete, the modified edible oil is obtained.
6. The method for preparing an adhesive using waste edible oil as raw material according to claim 5, characterized in that: In the step P3, the mass ratio of the edible oil, the tannic acid solution and the citric acid after rotary evaporation is 10:3-6:3-6.
7. The method for preparing an adhesive using waste edible oil as raw material according to claim 4, characterized in that: In the steps S1 and S2, the reaction conditions are 40-48°C, and in the step S3, the high-speed shear rate is 300-500 rpm / min, and the constant temperature is 28-35°C.
8. The method for preparing an adhesive using waste edible oil as raw material according to claim 5, characterized in that: In step P2, the mass ratio of waste cooking oil, 30% H2O2, formic acid and concentrated sulfuric acid is 1:0.7:0.2:0.
05.
9. The method for preparing an adhesive using waste edible oil as raw material according to claim 5, characterized in that: In step P3, the tannic acid solution may also be an ethanol solution with a concentration of 0.5 g / ml.